Resistance of salt marsh substrates to near‐instantaneous hydrodynamic forcing. Issue 1 (9th June 2020) - Brooks, Helen; Möller, Iris; Carr, Simon; Chirol, Clementine; Christie, Elizabeth; Evans, Ben; Spencer, Kate L.; Spencer, Tom; Royse, Katherine
Abstract: Salt marshes deliver vital ecosystem services by providing habitats, storing pollutants and atmospheric carbon, and reducing flood and erosion risk in the coastal hinterland. Net losses in salt marsh areas, both modelled globally and measured regionally, are therefore of concern. Amongst other controls, the persistence of salt marshes in any one location depends on the ability of their substrates to resist hydrodynamic forcing at the marsh front, along creek margins and on the vegetated surface. Where relative sea level is rising, marsh elevation must keep pace with sea‐level rise and landward expansion may be required to compensate for areal loss at exposed margins. This paper reviews current understanding of marsh substrate resistance to the near‐instantaneous (seconds to hours) forcing induced by hydrodynamic processes. It outlines how variability in substrate properties may affect marsh substrate stability, explores current understanding of the interactions between substrate properties and erosion processes, and how the cumulative impact of these interactions may affect marsh stability over annual to decadal timescales. Whilst important advances have been made in understanding how specific soil properties affect near‐instantaneous marsh substrate stability, less is known about how these properties interact and alter bulk substrate resistance to hydrodynamic forcing. Future research requires a more systematic approach to quantifying biological and sedimentological marsh substrate properties. These properties must then be linked to specific observable erosion processes, particularly at the marsh front and along creek banks. A better understanding of the intrinsic dynamics and processes acting on, and within, salt marsh substrates will facilitate improved prediction of marsh evolution under future hydrodynamic forcing scenarios. Notwithstanding the additional complications that arise from morphodynamic feedbacks, this would allow us to more accurately model the future potential protection from flooding and erosion afforded by marshes, while also increasing the effectiveness of salt marsh restoration and recreation schemes. © 2020 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : Salt marsh stability reflects, at least in part, the cumulative interaction of forcing and resistance over time. We review marsh resistance by outlining how substrate properties may affect marsh substrate stability, the spatial variation in these properties, and how they both affect, and are affected by, salt marsh processes. We then discuss how the cumulative impact of these interactions over annual to decadal timescales affects marsh stability.